Enhancing Quality of Life for Riverbank Communities in Rajshahi City - Hossan, Alomgir; Alom, Jahangir (MultiTech Publisher, 2024)
This study investigates strategies to enhance the quality of life for riverbank communities in Rajshahi City, Bangladesh, situated along the Padma River. Through a comprehensive analysis of socio-economic, environmental, governance, and community aspects, the study identifies key challenges and opportunities. Findings reveal pervasive socio-economic disparities, exacerbated by environmental degradation and governance shortcomings. Despite these challenges, the study highlights community resilience, and the potential of grassroots initiatives to effect positive change. The study emphasizes the importance of integrated and participatory approaches to address the multifaceted issues facing riverbank communities. By prioritizing socio-economic equity, environmental sustainability, and community empowerment, it is possible to create inclusive and resilient communities along the riverbanks of Rajshahi City.